Analisis Strategi Bersaing Pada UKM Laundry (Studi Kasus Pada Wijaya Laundry Kota Baturaja) - Destiarini, Destiarini; Wijaya, . Habibullah; Pratama, Riyan Andika; Kurniawan, Rifqi; Chandraloka, David; Mirando, Rahmat Dwiki (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to formulate an appropriate competitive strategy for Wijaya Laundry in Baturaja City through an analysis of internal and external factors and service quality. The research method used is descriptive qualitative with data collection techniques in the form of interviews and direct observation. Sampling was carried out purposively by involving 15 respondents consisting of the owners and customers of Wijaya Laundry. Data analysis was conducted using SWOT analysis to identify strengths, weaknesses, opportunities, and threats, as well as service quality analysis covering the aspects of physical evidence, reliability, responsiveness, assurance, and empathy. The results showed that Wijaya Laundry had a number of internal weaknesses, including the absence of clear business planning, unorganised financial management, unstructured task distribution, and limited promotional activities. Externally, opportunities were not being optimally utilised, particularly the use of digital technology as a promotional medium. In addition, service quality still needed to be improved, especially in terms of the comfort of business facilities. Based on the SWOT analysis results, the recommended competitive strategy is an intensive strategy in the form of market penetration through increased promotional activities, expansion of digital-based promotional reach, and the provision of customer loyalty programmes to increase competitiveness and maintain business sustainability.